The hangover trilogy [videorecording (Blu-Ray)] / Warner Bros. Pictures presents ; in association with Legendary Pictures ; a Green Hat Films production. - Phillips, Todd, 1970-; Cooper, Bradley; Helms, Ed; Galifianakis, Zach; Bartha, Justin; Graham, Heather, 1970-; Jeong, Ken, 1969-; Beck, Christophe, 1972-; Sher, Lawrence, 1970-; Neil-Fisher, Debra (Warner Bros. Entertainment, 2013)
Hangover: They planned a Vegas bachelor party that they would never forget. Now they really need to remember what exactly went down.